Opening Letter of RILEM TC MWP: Mechanical wave propagation to characterize bituminous mixtures - Jean-Claude Carret; Lucas Babadopulos (RILEM Technical Letters)
This technical letter investigates mechanical wave propagation (MWP) methods to characterize the stiffness of bituminous mixtures (BM), particularly using ultrasonic testing (UT) and impact resonance testing (IRT), as innovative alternatives to traditional quasi-static techniques. Recognizing the complexity of BM’s viscoelastic behavior influenced by temperature and frequency, the paper presents critical scientific and technological challenges to the newly started RILEM Technical Committee on MWP to characterize BM. By addressing the need for standardized testing procedures and data interpretation guidelines, the anticipated impact includes enhanced quality control and characterization capabilities that promote cost-effective pavement design. Furthermore, with this first effort on laboratory procedures, it is expected to facilitate future integration of non-destructive assessment methods into field practices, thus advancing the state-of-the-art in pavement engineering. This work aims to provide a robust framework for future research and practical applications in the characterization of bituminous materials.